Awareness and analysis: concurrent and predictive roles of two morphological processes in early reading comprehension - Zinger, Katharine; Kruk, Richard S. (Frontiers in Language Sciences, 2024)
We examine how awareness and analysis of morphemes contribute to children’s reading comprehension and its development. A multidimensional perspective on reading comprehension posits morphological awareness and morphological analysis play distinct roles in reading comprehension. Assuming individual differences in growth in these aspects of morphological processing, their concurrent influences can vary depending on children’s reading comprehension abilities, and predictive influences can change as children’s reading comprehension abilities improve. The current longitudinal study examined the concurrent and predictive influences of awareness and analysis on children’s reading comprehension from Grades 1 to 3. Data from 171 public school children, with diverse reading comprehension abilities, were collected across five waves and were analyzed using cross-lagged panel structural equation modeling. Results showed concurrent relationships among morphological awareness, analysis, and reading comprehension in Grades 1 and 2, with morphological analysis continuing to have a concurrent relationship with reading comprehension in Grade 3. Morphological awareness in all waves but Wave 3, at the end of Grade 2, predicted subsequent reading comprehension. Morphological analysis did not predict subsequent reading comprehension. Findings support the multidimensional conceptualization of awareness and analysis as distinct morphological processes that play early-wave concurrent and across-wave predictive roles in children’s reading comprehension development.